2018
DOI: 10.1016/j.jchromb.2018.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Bioanalysis of ibrutinib, and its dihydrodiol- and glutathione cycle metabolites by liquid chromatography-tandem mass spectrometry

Abstract: Ibrutinib is a targeted covalent inhibitor frequently used for the treatment of various lymphomas. In addition to oxidative metabolism, it is metabolized through glutathione coupling. The quantitative insight into this kind of metabolism is scarce, and tools for quantitation are lacking. The non-oxidative metabolism could prove a more prominent role when oxidative metabolism is impaired. Also, in-vitro studies could over-estimate the effect of CYP450-inhibition. To gain quantitative insight into this relativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 15 publications
1
21
0
Order By: Relevance
“…To the best of our knowledge, there are several publications with regard to the pharmacokinetics of ibrutinib . Ibrutinib was rapidly absorbed into the body after oral administration and reached its maximum plasma concentration at 1–2 h post‐dose with an elimination half‐life of 4–6 h .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, there are several publications with regard to the pharmacokinetics of ibrutinib . Ibrutinib was rapidly absorbed into the body after oral administration and reached its maximum plasma concentration at 1–2 h post‐dose with an elimination half‐life of 4–6 h .…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] Ibrutinib was rapidly absorbed into the body after oral administration and reached its maximum plasma concentration at 1-2 h post-dose with an elimination half-life of 4-6 h. 8 The primary metabolite of ibrutinib was dihydrodiolibrutinib. [9][10][11] This metabolite showed reversible inhibitory activity towards BTK, approximately 15 times lower than that of ibrutinib with plasma concentrations in the same range as ibrutinib levels. 4,12 In vitro experiments indicated that ibrutinib was extensively metabolized primarily by CYP3A4 and to a lesser extent by CYP2D6.…”
Section: Introductionmentioning
confidence: 99%
“…There have been several reports on the LC/MS analysis of ibrutinib in plasma (Beauvais et al, ; de Vries et al, ; Rood et al, ). All of the assays were based on the triple quadrupole mass spectrometer with selective reaction monitoring mode, which showed high sensitivity and selectivity.…”
Section: Resultsmentioning
confidence: 99%
“…The application of the method is not shown (Huynh et al, ). Rood et al () demonstrated the bioanalysis of ibrutinib, its dihydrodiol and glutathione metabolites in human plasma using LC‐ESI‐MS/MS. The chromatographic separation was performed on a Waters Acquity UPLC BEH C18 column using 0.1% formic acid and methanol as the mobile phase.…”
Section: Case Studiesmentioning
confidence: 99%